Fast filtration with a vacuum manifold system as a rapid and robust metabolome sampling method for Saccharomyces cerevisiae. (November 2021) - Yun, Eun Ju; Seo, Seung-Oh; Kwak, Suryang; Oh, Eun Joong; Lee, Sun-Hee; Jin, Yong-Su; Kim, Kyoung Heon
Graphical abstract: Highlights: For metabolome sample preparation, rapid quenching of cell metabolism is essential. Cold methanol quenching resulted in severe losses of intracellular metabolites. We developed a new fast filtration method using a vacuum manifold system. When using the fast filtration, most metabolites were highly preserved. This new fast filtration method can be applied to yeast metabolome analysis. Abstract: For metabolome sample preparation, rapid quenching of cellular metabolism without severe loss of intracellular metabolites is important. Here, we comparatively evaluated the two sampling methods, cold methanol quenching and fast filtration, for one of the most important industrial microorganisms, yeast Saccharomyces cerevisiae . The latter, using a vacuum manifold system capable of processing up to twenty samples simultaneously, was developed here. The results showed that the cold methanol quenching method resulted in severe losses of intracellular metabolites but that sugars and sugar phosphates were highly preserved. In comparison, the fast filtration method better preserved most metabolites with less extracellular contamination. Our results suggested that the fast filtration method with a vacuum manifold system can be widely applied to yeast metabolome analysis due to its simplicity, robustness, and lack of significant intracellular metabolite loss.